Simple rules of technical analysis and autoregressive models in the Chilean exchange market between 1995 and 2001 - Parisi F., Antonino; Parisi F., Franco; Cañas I., Enrique (Estudios de Administración, 2002)
In the Chilean exchange rate market, composed by sophisticated institutional investors and under different models of intervention of Central Bank, it is possible to obtain abnormal returns with the use of technical analysis and autoregresive models. The findings are similar to those observed in other international markets, but they were not the expected by the authors, since the low number of participants in this market, the high volatility due to deep international financial crises and the significant changes in this market introduced by the Central Bank. In effect, in the last third of the sample, the volatility of the exchange rate increased significantly and the abnormal returns obtained under the technical analysis and autoregressine models were equivalent to 60% approximately of the total sample. This period corresponds to the decision of the Chilean Central Bank to intervine in the exchange rate market as a result of the economic crisis in Argentina. Also, we did not observed statistical difference between the exchange rate and the forecasted by the autoregressive models, result that was validated by parametric and nonparametric test.